Lipopolysaccharide Prompts Oxidative Stress and Apoptosis in Rats’ Testicular Tissue - A Halawa Amal; A El-Adl Mohamed; F Hamed Mohamed; Z Balboula Ahmed; A Elmetwally Mohammed (Journal of Veterinary Healthcare, 2018)
Lipopolysaccharide (LPS) is a component of the outer membrane of gram negative bacteria. LPS challenging allows switching transcription of proinflammatory cytokines on via over stimulation of Toll-like receptors (TLRs) signaling pathway with subsequent pathogenic inflammatory response. We investigated the possible reproductive toxicity of LPS in male Wister albino rats. Oxidative stress markers, antioxidant status and caspase-3 activity were analyzed in testicular tissues of rats exposed to either saline or LPS (4 mg/kg BW, ip; 0.18 of the LD50). The samples were collected at 6 h and 72 h after injection of LPS. A significant reduction in testicular reduced glutathione (GSH), glutathione-S-transferase (GST) and superoxide dismutase (SOD) was observed at 72 h compared to control group. Total antioxidant capacity was decreased at 6 h with additional significant reduction at 72 h. Catalase activity was reduced significantly at both 6 and 72 h. Malondialdehyde (MDA) was increased (P ≤ 0.05) in LPS injected rats without variation between 6 and 72 h. A significant increase in nitric oxide (NO) was observed at 72 h after injection. A time-dependent increase in LPS-treated groups was observed in the concentration of caspase-3.Histopathological analysis revealed degenerative changes and necrosis of seminiferous tubules after 6 h with further accumulation of eosinophilic edematous transudate in its lumen after 72 h. In conclusion, by increasing time of exposure, LPS induced lipid peroxidation, oxidative stress, reduced testicular antioxidant capacity and encouraged testicular apoptosis which could be possible mechanisms for impairment of testicular function.
Keywords: Lipopolysaccharide